Functional analysis and treatment of elopement. - Piazza, C C (1997)
Elopement is a dangerous behavior because children who run away may encounter life-threatening situations (e.g., traffic). We conducted functional analyses of the elopement of 3 children who had been diagnosed with developmental disabilities. The results identified a maintaining reinforcer for the elopement of 1 child, but the data were difficult to interpret for 2 of the children. Subsequent reinforcer assessments were used to help to clarify the reinforcers for elopement for these 2 children. Results of the functional analyses and reinforcer assessments then were used to develop successful treatments to reduce elopement. The findings are discussed in terms of (a) the application of functional analysis methodology to elopement, (b) the use of reinforcer assessments to identify potential reinforcers when standard functional analyses are undifferentiated, and (c) the utility of assessment-based treatments for elopement.